2018
DOI: 10.1186/s12879-018-3210-x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of rickettsiae in Danish patients tested for Lyme neuroborreliosis: a retrospective study of archival samples

Abstract: BackgroundWith a prevalence of 4.7–13% in Danish Ixodes ricinus ticks, Rickettsia helvetica is one of the most frequently detected tick-borne organisms in Denmark. Most reports of human exposure have described asymptomatic seroconversion or a mild, self-limiting flu-like illness but it has also been implicated as a cause of subacute lymphocytic meningitis. Because Borrelia burgdorferi sensu lato (Bbsl) and R. helvetica are both found in the same tick species, potential co-transmission is a possibility. We exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…Both B. miyamotoi and R. helvetica have been found to be associated with (other) neurological disorders in previous studies, but not with facial paralysis as in this study [ 8 , 17 , 18 ]. Facial paralysis is a well-known clinical sign of Lyme neuroborreliosis and sometimes also TBE [ 19 23 ], but has not been associated with other TBPs.…”
Section: Discussionsupporting
confidence: 55%
“…Both B. miyamotoi and R. helvetica have been found to be associated with (other) neurological disorders in previous studies, but not with facial paralysis as in this study [ 8 , 17 , 18 ]. Facial paralysis is a well-known clinical sign of Lyme neuroborreliosis and sometimes also TBE [ 19 23 ], but has not been associated with other TBPs.…”
Section: Discussionsupporting
confidence: 55%
“…and serological methods for SFG rickettsiae, eight patients were found to be positive for Rickettsia spp. by PCR in the CSF, and most of them had symptoms and laboratory findings characteristic of LNB (Ocias et al, 2018). Rickettsia spp.…”
Section: Discussionmentioning
confidence: 99%
“…Several European studies, including those from Sweden (Bjöersdorff et al, 1999;Lindblom et al, 2013;Lindblom et al, 2016;Wass et al, 2018), have reported serological evidence of co-infections with different tick-borne pathogens in humans (Dunaj et al, 2018;Jahfari et al, 2016;Koetsveld et al, 2016;Moniuszko et al, 2014;Ocias et al, 2018;Panczuk et al, 2016). However, few of these studies have used molecular detection methods and the primary focus has not been on CNS infection.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, SFGR species were reported in co-infections with Borreli burgdorferi , Anaplasma phagocytophilum , Orientia tsutsugamushi and herpes simplex virus 2 [ 13 16 ]. In this study, we reported for the first time a tick bite patient co-infected with R .…”
Section: Introductionmentioning
confidence: 99%